Sport in Europe's era of austerity: crisis or adaptation?. Issue 1 (14th March 2017) - Roberts, Ken
Abstract : Purpose: The purpose of this paper is to assess whether European sport has been damaged or adapted during the austerity in public sector and consumer spending that has followed the financial crisis of 2008-2009. Design/methodology/approach: Review of literature and data. Findings: Sport has adapted successfully. Research limitations/implications: The overall conclusions will not apply to every sport in every country. Practical implications: Sport flourishes when it adapts to historical trends. Originality/value: Updates all previous reviews.